Półka literacka 2018 - Nęcka, Agnieszka (Postscriptum Polonistyczne, 2020)
The article presents the most important and the most interesting prose and poetry publications that appeared in 2018. Last year was marked by a dominance of well-known authors (such as: Marek Bieńczyk, Wiesław Myśliwski, Zyta Rudzka, Eustachy Rylski, Szczepan Twardoch, Krzysztof Varga, Janusz Pasterski, Marzanna Bogumiła Kielar, Eugeniusz Tkaczyszyn-Dycki) and proved that the Polish literary market was stable, but there was no place for new trends or spectacular literary debuts.